Application of arrhenius kinetics to evaluate oxidative stability in vegetable oils by isothermal differential scanning calorimetry - Tan, C. P.; Che Man, Y. B.; Selamat, J.; Yusoff, M. S. A. (Wiley, 2001)
In this study, 10 different vegetable oils were oxidized at four different isothermal temperatures (383, 393, 403, and 413 K) in a differential scanning calorimeter (DSC). The protocol involved oxidizing vegetable oils in a DSC cell with oxygen flow. A rapid increase in evolved heat was observed with an exothermic heat flow appearing during initiation of the oxidation reaction. From this resulting exotherm, the onset of oxidation time (To) was determined graphically by the DSC instrument. In our experimental data, linear relationships were determined by extrapolation of the log (To) against isothermal temperature. The rates of lipid oxidation were highly correlated with temperature. In addition, based on the Arrhenius equation and activated complex theory, reaction rate constants (k), activation energies (Ea), activation enthalpies (ΔH‡), and activation entropies (ΔS‡) for oxidative stability of vegetable oils were calculated. The Ea′, ΔH‡, and ΔS‡ for all vegetable oils ranged from 79 to −104 kJ mol−1, from 76 to −101 kJ mol−1, and from −99 to −20 J K−1 mol−1, respectively. Based on the results obtained, differential scanning calorimetry appears to be a useful new instrumental method for kinetic analysis of lipid oxidation in vegetable oil.